Supply chain model of Top One Trading : a study based on secondary data review and discussion with internal industry experts - Mishu, Sahida Sharmin Salim (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.